Paciente de sexo femenino de 40 años de edad que presenta obesidad mórbida y diabetes mellitus tipo ll. - Carreño Muentes, Jeniffer Lizbeth (2020)
The present clinical case is of a 40-year-old female patient who attended the health center due to prolonged dyspnea, undergoing an anthropometric evaluation, he was diagnosed with type III morbid obesity with a BMI: 47.7 kg / m2, he also had diabetes mellitus type ll having a glycemic alteration of 155 mg / dl in the fasting state and a glycosylated hemoglobin of 7.9%. I consider it important to mention the following clinical signs: Blood pressure 140 / 80mmHg, pulse 115 beats / min, respiratory rate 26 breaths / min, temperature 38.4 ° C. His laboratory tests indicate high values of cholesterol 255 mg / dl, triglycerides 162 mg / dl, LDL 142 mg / dl and HDL 70 mg / dl, these parameters determine dyslipidemia. As associated symptoms: constipation with persistence of 2 weeks, intense headache, sleep apnea, back pain, joints, and depressive disorders. A comprehensive assessment is carried out with the anthropometric, biochemical, clinical and dietary parameters, a norm caloric diet is prescribed low in complex carbohydrates with their selection, low in saturated fats, it includes mono-unsaturated and polyunsaturated fatty acids rich in omega 3 and 6, high content of soluble and insoluble dietary fiber, with a fraction of 5 meals a day and recommendation of moderate physical activity. After meeting the objectives set, new laboratory tests are analyzed, which shows a favorable result of glucose levels that decreased from 134mg / dl to 115mg / dl, also glycosylated hemoglobin with a reduction from 7.9% to 6.9 %, it was possible to improve the biochemical parameters of the lipid profile, a weight reduction of 7.7 kg was obtained with a BMI of 44.7 kg / m2. Key words: morbid obesity, diabetes mellitus, dyspnea, glycosylated hemoglobin, dyslipidemia.